PENGARUH PENGGUNAAN DESKRIPSI SINGKAT BERBAHASA INGGRIS PADA AKUN INSTAGRAM @FOLKATIVE TERHADAP EFEKTIVITAS PENYAMPAIAN INFORMASI - Nickie Renail Asmara (2024)
The Instagram account @folkative is an account that disseminates information about daily news. @folkative disseminates information using two languages, Indonesian in the headline of the information, while English in the short description which further complements the information. The use of short descriptions in English can cause misunderstandings or miscommunication regarding the information provided because there are readers who do not master English and feel it is too complicated if they have to translate it first. This research aims to examine the extent to which the use of short descriptions in English can influence the effectiveness of conveying information on the @folkative Instagram account. The research uses message design logic theory, with a quantitative method, survey approach, and explanatory research type. This research used followers of the Instagram account @folkative as the population and used an accidental sampling technique, with a sample size of 100 respondents. The results of the hypothesis test calculation state that t count is 16,014 > t table 1,948, which means that Ha is accepted. It can be concluded that variable X and variable Y have a large and significant influence. The results of the coefficient of determination test showed that the level of influence between variables was 72.4%, so the use of short descriptions in English on the @folkative Instagram account had a large and significant influence on the effectiveness of information delivery, then the regression coefficient number stated a value of 0.767 (positive).